APPLICATION OF CORRELATION-REGRESSION METHOD FOR RISK MANAGEMENT IN HIGHER EDUCATION INSTITUTIONS - Seriktayeva А.; Rakhmetullina Ж.; Mukasheva Р.; Mukhamedova Р. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2025)
The purpose of the work is to assess current risks in universities using mathematical methods. The decline in the number of applicants to regional universities of the country is one of the main risks in the strategic development program. The conditions that could affect this risk were identified, and a regression analysis was performed based on the data obtained. For completeness of the results obtained, the correlation and regression method was used. A unified system of indicators has been created through the signs and features of economic, social, personal and information factors of accessibility of higher education. As a result of the study, a regression equation was created and the amount of risk was calculated, the significance of the constructed models was assessed, and the interpretation of the results obtained in the modeling process was given. The theoretical and methodological significance of the study lies in improving the methodology by substantiating the possibility of using correlation and regression analysis and economic and mathematical modeling.